If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -7 = 3 + 7x Reorder the terms: -7 + 12x = 3 + 7x Solving -7 + 12x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -7 + 12x + -7x = 3 + 7x + -7x Combine like terms: 12x + -7x = 5x -7 + 5x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -7 + 5x = 3 + 0 -7 + 5x = 3 Add '7' to each side of the equation. -7 + 7 + 5x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + 5x = 3 + 7 5x = 3 + 7 Combine like terms: 3 + 7 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 9-2k=17-4k | | 8(2x+1)=2(3x+4)+2(4x+3) | | 3m=54 | | 4-15+45=0 | | 6y^2-y=0 | | 7x=2xsquared | | X-5=2x-14 | | 2xsquared=7x | | -30.2+13.2+(-3.2)= | | 0.97y-0.29=0.83 | | 6x-16=70 | | 96=(12+2x)(8+2x) | | c^2+17c=-72 | | 12.78+2.75x=5.26+7.23 | | b^2-8b=33 | | 6.26x-54.89=0.86x+9.76 | | y^2+19y+34=0 | | 12-4x=3(2x+27) | | 2x+5y=112 | | 1-3(x-2)=2-7(1-x) | | 4x+8+2x=2x-24 | | 2(x-3)=-7(1-x) | | 4x+8+2=2x-24 | | 17x+2y=69 | | 17x+Y=69 | | (5-2y-3x)dy=(2x+3y-5)dx | | 2(-2+4)+6*-2=2(2+3*-2) | | 7n+3=10n-1 | | -12+-9=3(2+-9) | | (m-3)=4m-5 | | y=-0.25x+15 | | 0.3x-0.4=-0.3x+1.4 |